Judicialização e representações sociais : um estudo sobre os meios processuais de coibir o abuso no acesso ao judiciário - Silva, Rayla Mariana Figueiredo (2018)
The great driving doubt that gives rise to this masters dissertation concerns the possibility of state action outside the constitutionally established limits. In this sense, the state would be acting in excess and fortifying the social representations of domination insculpated in the jurisdictional ones, in order to make them individuals dependent on the state arbitrariness, and invariably without decisive power for having given their share of power to that which should only guarantee peace and social balance. In order to develop the study proposed here, it was attempted to carry out a division of chapters organized so as to first analyze the governmental relations and the way in which the phenomenon of power is manifested as a common element to the political regimes, as well as the consequences of social representations envisioned in contemporary society, based on Pierre Bourdieu, Axel Honneth and Erving Goffman. In the next chapter, it is analyzed the possibility that with the judiciary's distortion of the power that had been conferred on it by the individuals who wanted its protection and assistance, there was an opening in our order for the establishment of the judicialization. This, considered as the action in disagreement with the constitutional normative standards, makes judiciary the simplest relations of life in society, which do not necessarily need to be submitted to state arbitration. It is known that with the establishment of the Federal Constitution of 1988 a wide range of rights has been protected, thus allowing the judgment of the claim of anyone who wishes to see their right satisfied before the judiciary. However, some of the issues could, as effectively, be solved through out-of-court propositions, which would encourage individuals to act positively and actively, reversing the apathy characteristic of the pathologies mentioned in the previous chapter. Finally, in the last chapter, the possibility of restricting this excessive use of state jurisdiction is analyzed, in view of mechanisms for restraining the judicialization already provided for in the civil procedural law, such as the application of fines for bad faith litigation, use of special courts of conscience with the payment of costs by those who do not have the benefit of the gratuitous justice and the direction of the effective and gratuitous jurisdictional rendering to those who in fact prove to be hypersufficient.